Unveiling Indonesia's Independent Curriculum: a Bibliometric Exploration - Yusmadi, Yusmadi; Permana, Johar; Herawan, Endang; Sutarsih, Cicih (Tadbir : Jurnal Studi Manajemen Pendidikan, 2024)
Based on the data analyzed, the Independent Curriculum has gained significant scholarly attention, with a rapid increase in publications from 2022 to 2024, particularly focusing on its application in primary education, personalized learning, and culturally contextualized teaching practices such as Islamic education. Key contributors to this research are concentrated in Indonesian public universities, with some international collaboration, highlighting the curriculum's national relevance. The thematic clusters identified in the analysis reveal strong trends in project-based learning, differentiated instruction, and cultural preservation, demonstrating the curriculum's versatility and adaptability across different educational levels and contexts. However, gaps remain in long-term outcome studies, equitable access to personalized learning, and broader cultural implementation, providing opportunities for future research to address these critical areas. This research indicates that several themes regarding the Independent Curriculum still warrant exploration, including studies on the implementation and outcomes of the curriculum across various levels of education, examinations of personalized and differentiated instruction within the curriculum, and investigations into the cultural and contextual adaptation of the Independent Curriculum. Addressing these areas will contribute to a more comprehensive understanding of the curriculum's impact and effectiveness in diverse educational settings.